A PEO-based composite solid electrolyte and its preparation method and application

By using PEO-based composite solid electrolyte in lithium-ion batteries and combining technical means of MOFs and ionic liquids, the problems of low conductivity, poor interface contact and narrow electrochemical stability window are solved, and the effects of high conductivity, good interface contact and wide electrochemical stability window are achieved.

CN114243088BActive Publication Date: 2025-04-08GUANGZHOU UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111411151.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-25
Publication Date
2025-04-08
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

The existing solid electrolytes have low conductivity, poor interface contact and narrow electrochemical stability windows, making it difficult to meet the needs of lithium-ion batteries in terms of high energy density and safety.

Method used

The PEO-based composite solid electrolyte is used, consisting of PEO, MOFs (such as ZIF-8), lithium salts and ionic liquids (ILs). The nano-scale MOFs particles and lithium salts are uniformly distributed in PEO by solution mixing, and ionic liquids are added to form a multi-ion channel network.

Benefits of technology

It significantly improves the room temperature conductivity and lithium ion migration number, improves the interface contact, and broadens the electrochemical stability window, so that the battery can operate stably in both room temperature and high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114243088B_ABST
    Figure CN114243088B_ABST
Patent Text Reader

Abstract

The present invention discloses a PEO-based composite solid electrolyte and a preparation method and application thereof. The electrolyte consists of PEO, MOFs, lithium salt and ionic liquid. The present invention adopts a solution mixing method to evenly distribute nano-scale MOFs particles and lithium salt in PEO, add ionic liquid as a plasticizer thereto to form a multi-ion channel network, and finally pour the PEO mixed solution into a mold and dry it to obtain a composite solid electrolyte. The composite solid electrolyte can stably operate normal pressure and high voltage batteries at room temperature, and can stably operate in a high temperature environment where liquid electrolytes are difficult to operate, and has great application prospects in the field of new energy solid-state energy storage batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid electrolytes in lithium ion batteries, and specifically relates to a PEO-based composite solid electrolyte and a preparation method and application thereof. Background Art

[0002] Energy has injected a strong impetus into the development of modern society, played a vital role in the prosperity and development of the economy and society, and greatly promoted the progress of society. For a long time, traditional fossil energy, as the main source of energy, has created a lot of social wealth while also causing a series of economic, social and environmental problems. As a non-renewable energy, facing the growing energy demand, the exploitable reserves of traditional fossil energy are facing exhaustion in the near future; in the process of production and use, a large amount of greenhouse gases and hazardous wastes are inevitably produced, which directly threatens the survival and development of human beings. Governments of various countries have raised energy security to the national strategic level. Therefore, the development and utilization of new energy has become a global consensus. Clean energy such as wind energy, solar energy, tidal energy, geothermal energy, etc. are renewable and pollution-free. To develop and utilize new energy safely and efficiently, advanced energy storage and conversion devices are indispensable. As a new type of efficient energy storage device, lithium-ion batteries have the outstanding advantages of high energy density, high output power, flexible operation and light volume, which are of great significance to the new energy industry. At present, liquid organic electrolytes are commonly used in lithium-ion batteries, which have safety risks such as leakage, flammability and explosion. In recent years, many reported battery fire and explosion incidents have aroused people's attention to the safety of new energy batteries. In addition, liquid electrolytes seriously restrict the battery structure design and cannot fully meet the market's various personalized needs for batteries. Solid-state lithium batteries do not contain liquid organic electrolytes, which perfectly overcomes a series of safety and process problems brought by organic electrolytes, greatly improves the mechanical properties and stability of the battery, and has significant safety.

[0003] Solid electrolyte solid lithium batteries have the advantages of high safety, high energy density, low self-discharge, and high temperature resistance. They can avoid the side effects of liquid electrolytes and improve the service life and safety of batteries. Solid electrolyte batteries that are easy to form films and stack are easy to package and easy to achieve high-voltage integration and large-scale production. In addition, compared with electrolytes, most electrolytes have higher lithium ion migration numbers, which can effectively solve the concentration polarization problem of batteries. However, compared with traditional organic electrolytes, solid electrolytes still have many problems. Although sulfide electrolytes have room temperature conductivity comparable to organic electrolytes, they have extremely high requirements for preparation and use conditions, poor environmental stability, and are not practical; ceramic oxide electrolytes have a rigid interface and large interface resistance that is difficult to overcome, and the preparation process is complex and the cost is high; polymer electrolytes have inherent advantages in interface contact, good film forming properties and flexibility, and show good application prospects in flexible wearable electronic devices, but polymer electrolytes have low conductivity at room temperature, which seriously restricts their application.

[0004] Combining polymer electrolytes and inorganic particles to construct a rigid and flexible composite structure, combining the two, and complementing each other's strengths is one of the feasible solutions to solve the problems of low conductivity and poor interface contact of solid electrolytes. Among many solid electrolytes, PEO (polyethylene oxide)-based polymer solid electrolytes have the highest conductivity among polymer electrolytes. At the same time, they have the advantages of high safety, mechanical flexibility, viscoelasticity and easy film formation. They are generally considered to be one of the most promising solid electrolytes. The working mechanism of PEO is mainly that lithium ions continuously undergo a complexation-decomplexation process with the ether oxygen bonds in the long chain of PEO, and lithium ion migration is achieved by the movement of PEO chain segments. Therefore, the mobility of PEO chain segments largely determines the ionic conductivity of PEO-based solid electrolytes. However, pure PEO has high crystallinity at room temperature, low solubility of lithium salts in the amorphous phase, and low carrier concentration, resulting in a small lithium ion migration number. The room temperature ionic conductivity of PEO-based electrolytes is only 10 -7 S cm -1 . Metal organic frameworks (MOFs) are a new type of porous coordination polymer with a large specific surface area and abundant Lewis acid-base centers. MOFs as fillers for PEO polymer electrolytes can interact with new large anion-containing lithium salts, effectively increasing the dissociation of lithium salts and the segmental mobility of polymers, enhancing the mobile ions and migration pathways, and thus improving lithium ion conductivity. At the same time, the addition of inorganic particles also improves the mechanical strength of the electrolyte to a certain extent. For example, Liu et al. achieved a solid electrolyte conductivity of 7.36×10 -6 S cm -1 Increased to 3.16×10 -5 S cm -1However, simply adding MOFs will reduce the conductivity of the electrolyte due to the agglomeration between inorganic particles. The interface problem between inorganic particles and PEO cannot be ignored. In the face of the current mainstream high-voltage electrode materials, it is necessary to broaden their electrochemical stability window. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of existing solid electrolytes, such as low conductivity, poor interface contact, and narrow electrochemical stability window, and to provide a PEO-based composite solid electrolyte with high conductivity.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned PEO-based composite solid electrolyte.

[0007] Another object of the present invention is to provide an application of the above-mentioned PEO-based composite solid electrolyte.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A PEO-based composite solid electrolyte consists of PEO, MOFs, lithium salt and ionic liquid (IL).

[0010] The MOFs are preferably ZIF-8 nanoparticles.

[0011] The lithium salt is preferably lithium bis(trifluoromethanesulfonyl)imide.

[0012] The ionic liquid is preferably 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0013] The preparation method of the above-mentioned PEO-based composite solid electrolyte is to uniformly distribute nano-scale MOFs particles and lithium salt in PEO by solution mixing method, add ionic liquid as a plasticizer thereto to form a multi-ion channel network, and finally pour the PEO mixed solution into a mold and dry it to obtain a composite solid electrolyte; preferably, it includes the following steps:

[0014] (1) Preparation of ZIF-8 nanoparticles: dissolving zinc salt in solvent A to obtain solution A; dissolving 2-methylimidazole in solvent B to obtain solution B; ultrasonically treating solution A and solution B, mixing them, stirring at a constant temperature, and standing them to separate the solid from the liquid; washing and drying the obtained solid to obtain ZIF-8 nanoparticles;

[0015] (2) Preparation of ionic liquid: lithium salt and 1-ethyl-3-methylimidazolium bromide are mixed in a molar ratio of 1:1.1 to 1.3, solvent C is added to dissolve, stirred at a constant temperature, and allowed to stand. After the solution is separated into layers, the lower layer of oily liquid is taken out for washing, and then dried to remove the residual solvent to obtain a pure ionic liquid;

[0016] (3) Preparation of composite solid electrolyte: lithium salt and ionic liquid are added to solvent D. After they are completely dissolved, ZIF-8 nanoparticles are added. After the ZIF-8 nanoparticles are evenly dispersed, PEO is added. The mixture is stirred at a constant temperature and then poured into a mold and dried to obtain a PEO-based composite solid electrolyte.

[0017] The zinc salt described in step (1) is preferably zinc nitrate hexahydrate.

[0018] The zinc salt and the 2-methylimidazole in step (1) are preferably mixed in a mass ratio of 1:3.5 to 4.5; more preferably in a mass ratio of 1:4.

[0019] The solvent A described in step (1) is preferably at least one of water and methanol; more preferably methanol.

[0020] The solvent B described in step (1) is preferably at least one of water and methanol; more preferably methanol.

[0021] The conditions of the ultrasonic treatment in step (1) are preferably: 200-400W for 10-30 minutes; more preferably 300W for 25 minutes.

[0022] The ultrasonic treatment in step (1) is performed at room temperature.

[0023] The room temperature is 15-35°C, more preferably 25-30°C.

[0024] The stirring conditions described in step (1) are as follows: temperature of 45-55°C, rotation speed of 250-400 rpm, and stirring time of 3-5 hours; more preferably as follows: temperature of 50°C, rotation speed of 300 rpm, and stirring time of 4 hours.

[0025] The standing time in step (1) is 20 to 28 hours, more preferably 24 hours.

[0026] The solid-liquid separation method in step (1) is preferably centrifugation.

[0027] The centrifugal condition is preferably 8000-10000 rpm for 3-10 min; more preferably 9000 rpm for 5 min.

[0028] The solution used in the washing in step (1) is preferably methanol.

[0029] The number of washings in step (1) is preferably 2 to 4 times; more preferably 3 times.

[0030] The drying in step (1) is preferably performed at 50-70°C for 36-60 hours, followed by grinding, and then drying at 90-100°C for 10-15 hours; more preferably, the drying is performed at 60°C for 48 hours, followed by grinding, and then drying at 100°C for 12 hours.

[0031] The lithium salt described in step (2) is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0032] The solvent C described in step (2) is deionized water.

[0033] The constant temperature stirring conditions described in step (2) are preferably as follows: temperature of 60-80°C, stirring time of 20-28 hours, and rotation speed of 250-350 rpm; more preferably as follows: temperature of 70°C, stirring time of 24 hours, and rotation speed of 300 rpm.

[0034] The standing time in step (2) is 20 to 28 hours, more preferably 24 hours.

[0035] The number of washing steps in step (2) is no less than three times.

[0036] The solution used in the washing described in step (2) is deionized water.

[0037] The degree of washing in step (2) is as follows: after washing, the upper aqueous solution is dripped with a nitrate solution. If no white precipitate is generated, it indicates that the washing is complete. If a white precipitate is generated, it indicates that the washing is inadequate and further washing is required.

[0038] The drying conditions described in step (2) are drying in a vacuum drying oven at 100-140° C. for 8-16 hours, preferably drying in a vacuum drying oven at 120° C. for 12 hours.

[0039] The solvent D described in step (3) is preferably anhydrous acetonitrile.

[0040] The lithium salt described in step (3) is preferably a dried lithium salt.

[0041] The lithium salt is preferably lithium bis(trifluoromethanesulfonyl)imide.

[0042] The drying is preferably performed under vacuum at 100° C. for 24 hours.

[0043] The PEO described in step (3) is the PEO after drying.

[0044] The drying is preferably performed under vacuum at 60° C. for 24 hours.

[0045] The PEO described in step (3) preferably has a molecular weight of 500,000 to 700,000; more preferably has a molecular weight of 600,000.

[0046] The molar ratio of PEO to lithium salt in step (3) is 17-19:1, preferably 18:1.

[0047] The amount of ZIF-8 nanoparticles used in step (3) is 0-25% (excluding the endpoint value 0) of the sum of the mass of PEO and lithium salt; preferably 20%.

[0048] The amount of the ionic liquid in step (3) is 19-21% of the total mass of PEO, lithium salt and MOFs; more preferably 20% of the total mass of PEO, lithium salt and MOFs.

[0049] The conditions for the constant temperature stirring in step (3) are as follows: temperature of 40-50°C, stirring time of 20-30h, and rotation speed of 200-300rpm; preferably as follows: temperature of 45°C, stirring time of 24h, and rotation speed of 230rpm.

[0050] The mold described in step (3) is preferably a polytetrafluoroethylene mold.

[0051] The polytetrafluoroethylene mold is preferably a polytetrafluoroethylene-shaped groove with a size of 7.5×7.5×2.0 mm.

[0052] The casting method is a tape casting method.

[0053] The drying in step (3) is preferably performed first in a glove box and then in a vacuum drying oven.

[0054] The drying in the glove box is to place the mold containing the mixed solution in the glove box for 12 to 48 hours to naturally evaporate most of the solvent.

[0055] The placement time is preferably 24 hours.

[0056] The glove box is in an argon atmosphere, with water and oxygen concentrations controlled below 0.1 ppm.

[0057] The drying temperature in the vacuum drying oven is 40-60°C, preferably 50°C.

[0058] The drying time in the vacuum drying oven is 36 to 72 hours, preferably 48 hours.

[0059] A PEO-based composite solid electrolyte is obtained by the above preparation method.

[0060] The above-mentioned PEO-based composite solid electrolyte is used in the manufacture of batteries.

[0061] The beneficial effects of the present invention are as follows:

[0062] 1. Compared with pure PEO-based polymer electrolytes, the addition of MOFs to the PEO-based composite solid electrolyte of the present invention destroys the PEO crystalline region, expands its amorphous region, promotes the movement of PEO chains, significantly improves its room temperature conductivity and lithium ion migration number, significantly improves the interface contact, and also enhances its mechanical strength to a certain extent, enhancing its safety in the battery.

[0063] 2. The preparation method of the PEO-based composite solid electrolyte of the present invention adopts the tape casting method, which has reliable process and prepares the ZIF-8 / IL / PEO composite solid electrolyte. The unique large specific surface area and porous structure of MOFs contain a large number of Lewis acid-base centers, which greatly promote the dissolution of lithium salts. The ionic liquid has good room temperature conductivity and a wide electrochemical stability window. After being added, it fills the pores of MOFs to form a new lithium ion migration network channel. During the battery assembly process, the overflowing ionic liquid has a wetting effect at the interface, effectively improving the interface contact. The prepared PEO-based composite solid electrolyte can stably operate normal pressure and high voltage batteries at room temperature, and can stably operate in a high temperature environment where liquid electrolytes are difficult to operate. It has great application prospects in the field of new energy solid-state energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 The XRD and SEM images of ZIF-8 of the present invention are shown in FIG. 1 , wherein (a) is the XRD image, (b) is the SEM image, and (c) is the XRD diffraction peak image of ZIF-8 and the standard simulation card.

[0065] Figure 2 This is a SEM image of the ZIF-8 / IL / PEO composite solid electrolyte of the present invention.

[0066] Figure 3 1 and 2 are XRD diagrams of the ZIF-8 / IL / PEO composite solid electrolyte of the present invention; wherein (a) is the XRD diagram of the composite solid electrolyte with different MOFs addition ratios, and (b) is a partial enlarged diagram of (a).

[0067] Figure 4 It is the EIS spectrum of IL / PEO of the present invention; A is a solid electrolyte containing no MOFs and containing 10wt% ionic liquid, B is a solid electrolyte containing no MOFs and containing 20wt% ionic liquid, and C is a solid electrolyte containing no MOFs and containing 20wt% ionic liquid.

[0068] Figure 5The EIS diagram of the ZIF-8 / IL / PEO solid electrolyte at room temperature and the conductivity diagram at different temperatures of the present invention; wherein, the curves in (a) are CPE20, CPE15, CPE25, CPE10, and CPE5 from left to right; the curves in (b) are CPE20, CPE15, CPE10, CPE25, CPE5, and CPE0 from top to bottom with the point at the horizontal axis of 70; (c) is a scatter plot of the logarithm of the conductivity (σ) and the temperature of 1000 / T.

[0069] Figure 6 It is a lithium ion migration number diagram of the ZIF-8 / IL / PEO composite solid electrolyte of the present invention; wherein, (a) is the current-time diagram of CPE20 constant current polarization, (b) is the impedance diagram before and after CPE20 polarization, (c) is the current-time diagram of CPE0 constant current polarization, (d) is the impedance diagram before and after CPE0 polarization, and (e) is the lithium ion migration number of solid electrolytes with different proportions.

[0070] Figure 7 This is the LSV test diagram of the ZIF-8 / IL / PEO composite solid electrolyte of the present invention; wherein the curves from top to bottom are CPE*20, CPE0 and CPE20 respectively.

[0071] Figure 8 This is a test diagram of the interface stability of the ZIF-8 / IL / PEO composite solid electrolyte of the present invention.

[0072] Fig. 9 The figure is a performance comparison diagram of the PEO-based composite solid electrolyte of the present invention and the control PEO-based polymer electrolyte applied to half-cells. DETAILED DESCRIPTION

[0073] The present invention is further described in detail below through specific implementation cases and accompanying drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art are all within the scope of the claims attached to this application.

[0074] Unless otherwise specified, all raw materials and reagents of the present invention are raw materials and reagents from the conventional market.

[0075] Example 1

[0076] Preparation of PEO-based composite solid electrolyte CPE20:

[0077] 1. Preparation of ZIF-8 nanoparticles

[0078] 1.0g of Zn(NO3)2·6H2O (zinc nitrate hexahydrate) and 4.0g of 2-methylimidazole were stirred and dissolved in 40mL of methanol (99.98%, analytical grade) solution, and ultrasonically treated (300W) for 25 minutes to obtain a uniformly dispersed transparent clear solution; the two were mixed, and the mixed solution was stirred at 50°C and 300rpm for 4 hours, and then aged at room temperature for 24 hours to complete the precipitation. Centrifugal separation was performed at 9000rpm for 5min to obtain a white precipitate, which was washed with methanol, centrifuged three times, and then vacuum dried at 60°C for 48 hours. After being taken out and fully ground, it was vacuum dried at 100°C for 12 hours to completely remove the residual moisture in the ZIF-8 pores to obtain ZIF-8 nanoparticles, which were transferred into a glove box for storage.

[0079] 2. Preparation of ionic liquids

[0080] 2.871 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1.911 g of 1-ethyl-3-methylimidazolium bromide (EMIMBr) were mixed in a molar ratio of 1:1, and 20 mL of deionized water was added to dissolve the mixture. The mixture was stirred at a constant temperature of 70°C (300 rpm) for 24 hours, and allowed to stand at room temperature for 24 hours. After the solution was separated, the lower layer of oily liquid was taken, and the separated liquid was washed three times with deionized water. The last supernatant was added with silver nitrate solution, and no white precipitate was generated, indicating that the ionic liquid had been washed clean and did not contain other impurity ions. After the detection was completed, the obtained ionic liquid was placed in a vacuum drying oven at 120°C for 12 hours to completely remove the residual moisture to obtain a pure ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (EMIM-TFSI), which was then transferred to a glove box for storage.

[0081] 3. Preparation of PEO-based composite solid electrolyte CPE20

[0082] PEO with a molecular weight of 600,000 was vacuum dried at 60°C for 24 hours and then transferred to a glove box, and lithium bistrifluoromethanesulfonyl imide (LiTFSI) was vacuum dried at 100°C for 24 hours and then transferred to a glove box, where the water and oxygen concentrations in the glove box were controlled below 0.1 ppm. According to a molar ratio of 18:1, 0.881 g of PEO and 0.319 g of LiTFSI were weighed, 0.24 g of the ZIF-8 nanoparticles prepared in step 1 were weighed according to 20% of the sum of the mass of PEO and LiTFSI, and 0.288 g of the ionic liquid prepared in step 2 was weighed according to 20% of the sum of the mass of PEO, LiTFSI and ZIF-8. LiTFSI was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, ZIF-8 nanoparticles were added and stirred for 4 hours. After the ZIF-8 nanoparticles were evenly distributed in the solution, PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45° C. for 24 hours, and the rotation speed was set to 230 rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method, and dried in a glove box for 24 hours to naturally evaporate most of the acetonitrile to obtain a PEO-based composite solid electrolyte. The PEO-based composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50° C. for 48 hours to completely remove the residual acetonitrile solvent. The dried composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and stored in a glove box to obtain a PEO-based composite solid electrolyte CPE20 with a ZIF-8 addition amount of 20%. After physical characterization and electrochemical testing, the surface of CPE20 was smooth and flat, MOFs were evenly dispersed without obvious agglomeration, and the conductivity at room temperature was 4.9×10 -5 S / cm, the lithium ion transference number is 0.48, and the conductivity is as high as 1.0×10 at 60°C. -3 S / cm.

[0083] Example 2

[0084] Preparation of PEO-based composite solid electrolyte CPE5

[0085] Take the PEO treated in Example 1 and the ZIF-8 nanoparticles and ionic liquid prepared in Example 1, and weigh 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) at a molar ratio of 18:1, weigh 0.06 g of ZIF-8 nanoparticles calculated as 5% of the sum of the mass of PEO and LiTFSI, and weigh 0.252 g of ionic liquid calculated as 20% of the sum of the mass of PEO, LiTFSI and ZIF-8. LiTFSI was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, ZIF-8 nanoparticles were added and stirred for 4 hours. After the ZIF-8 nanoparticles were evenly distributed in the solution, PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45°C for 24 hours, and the rotation speed was set to 230rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50°C for 48 hours to completely remove the residual acetonitrile solvent to obtain a PEO-based composite solid electrolyte. The dried PEO-based composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and placed in a glove box for storage to obtain a PEO-based composite solid electrolyte CPE5 with a ZIF-8 addition amount of 5%. The conductivity of CPE5 at room temperature is 1.1×10 -5 S / cm, and the lithium ion transference number is 0.40.

[0086] Example 3

[0087] Preparation of PEO-based composite solid electrolyte CPE10

[0088] Take the PEO treated in Example 1 and the ZIF-8 nanoparticles and ionic liquid prepared in Example 1, and weigh 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) at a molar ratio of 18:1, weigh 0.12 g of ZIF-8 nanoparticles calculated as 10% of the sum of the mass of PEO and LiTFSI, and weigh 0.264 g of ionic liquid calculated as 20% of the sum of the mass of PEO, LiTFSI and ZIF-8. LiTFSI was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, ZIF-8 nanoparticles were added and stirred for 4 hours. After the ZIF-8 nanoparticles were evenly distributed in the solution, PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45° C. for 24 hours, and the speed was set to 230 rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50° C. for 48 hours to completely remove the residual acetonitrile solvent to obtain a PEO-based composite solid electrolyte. The dried PEO-based composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and placed in a glove box for storage to obtain a PEO-based composite solid electrolyte CPE10 with a ZIF-8 addition amount of 10%. The conductivity of CPE10 at room temperature is 1.8×10 -5 S / cm, and the lithium ion transference number is 0.44.

[0089] Example 4

[0090] Preparation of PEO-based composite solid electrolyte CPE15

[0091] Take the PEO treated in Example 1 and the ZIF-8 nanoparticles and ionic liquid prepared in Example 1, and weigh 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) at a molar ratio of 18:1, and weigh 0.18 g of ZIF-8 nanoparticles calculated as 15% of the sum of the mass of PEO and LiTFSI, and weigh 0.276 g of ionic liquid calculated as 20% of the sum of the mass of PEO, LiTFSI and ZIF-8. LiTFSI was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, ZIF-8 nanoparticles were added and stirred for 4 hours. After the ZIF-8 nanoparticles were evenly distributed in the solution, PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45° C. for 24 hours, and the rotation speed was set to 230 rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50° C. for 48 hours to completely remove the residual acetonitrile solvent to obtain a PEO-based composite solid electrolyte. The dried PEO-based composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and placed in a glove box for storage to obtain a PEO-based composite solid electrolyte CPE15 with a ZIF-8 addition amount of 15%. The conductivity of CPE15 at room temperature is 2.7×10 -5 S / cm, and the lithium ion transference number is 0.46.

[0092] Example 5

[0093] Preparation of PEO-based composite solid electrolyte CPE25

[0094] Take the PEO treated in Example 1 and the ZIF-8 nanoparticles and ionic liquid prepared in Example 1, and weigh 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) in a molar ratio of 18:1, and weigh 0.3 g of ZIF-8 nanoparticles calculated according to 25% of the sum of the mass of PEO and LiTFSI, and weigh 0.3 g of ionic liquid calculated according to 20% of the sum of the mass of PEO, LiTFSI and ZIF-8. LiTFSI was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, ZIF-8 nanoparticles were added and stirred for 4 hours. After the ZIF-8 nanoparticles were evenly distributed in the solution, PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45° C. for 24 hours, and the rotation speed was set to 230 rpm. After PEO was completely dissolved, the PEO mixed solution was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally volatilize most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50° C. for 48 hours to completely remove the residual acetonitrile solvent to obtain a PEO-based composite solid electrolyte. The dried PEO-based composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and stored in a glove box to obtain a PEO-based composite solid electrolyte CPE25 with a ZIF-8 addition amount of 25%. The conductivity of CPE25 at room temperature is 2.5×10 -5 S / cm, and the lithium ion transference number is 0.42.

[0095] Comparative Example 1

[0096] According to the molar ratio of 18:1, 0.881g of PEO and 0.319g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were weighed, and LiTFSI was added to a beaker containing 20ml of analytical pure anhydrous acetonitrile. After stirring to fully dissolve, PEO was slowly added in two batches after complete dissolution, and stirring was performed while adding. After the addition was completed, constant temperature stirring was performed at 45°C for 24 hours, and the speed was set to 230rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50°C for 48 hours to completely remove the residual acetonitrile solvent. The dried solid electrolyte was punched into a circular sheet with a diameter of 19mm and stored in a glove box to obtain the added solid electrolyte A. The conductivity of A at room temperature was 5.1×10 -7 S / cm.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that this comparative example does not contain ZIF-8, but only contains 10% ionic liquid, and the ionic liquid is calculated as 10% of the sum of the mass of PEO and lithium salt. The specific preparation steps are as follows:

[0099] Take the PEO and ionic liquid in Example 1, according to the molar ratio of 18:1, weigh 0.881g of PEO and 0.319g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), and weigh 0.12g of ionic liquid according to 10% of the sum of the mass of PEO and lithium salt. Add lithium salt to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, stir until fully dissolved, then add ionic liquid, and slowly add PEO in two batches after the ionic liquid is evenly dispersed in the solution, stirring while adding. After the addition is completed, stir at a constant temperature of 45°C for 24 hours, and the speed is set to 230rpm. After PEO is completely dissolved, cast the PEO mixture into a smooth and flat polytetrafluoroethylene mold by casting. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, transfer the composite solid electrolyte to a vacuum drying oven and vacuum dry at 50°C for 48 hours to completely remove the residual acetonitrile solvent. Cut the dried solid electrolyte into circular sheets with a diameter of 19 mm and store them in a glove box to obtain a solid electrolyte B with an ionic liquid addition of 10%. AC impedance test B has a conductivity of 8.3×10 -7 S / cm.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that this comparative example does not contain ZIF-8, but contains 20% ionic liquid, which is calculated as 20% of the sum of the mass of PEO and lithium salt. The specific preparation steps are as follows:

[0102] According to a molar ratio of 18:1, 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) were weighed, and 0.24 g of ionic liquid was weighed according to 20% of the sum of the mass of PEO and the lithium salt. Add lithium salt to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, stir until fully dissolved, then add ionic liquid, and slowly add PEO in two batches after the ionic liquid is evenly dispersed in the solution, stirring while adding. After the addition is completed, stir at a constant temperature of 45°C for 24 hours, and the speed is set to 230rpm. After PEO is completely dissolved, cast the PEO mixture into a smooth and flat polytetrafluoroethylene mold by casting, dry in a glove box for 24 hours to naturally evaporate most of the acetonitrile, transfer the composite solid electrolyte to a vacuum drying oven and vacuum dry at 50°C for 48 hours to completely remove the residual acetonitrile solvent, punch the dried composite solid electrolyte into a circular sheet with a diameter of 19 mm and store it in a glove box to obtain a composite solid electrolyte C with an ionic liquid addition of 20%. AC impedance test C has a conductivity of 1.7×10 -6 S / cm.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 1 is that this comparative example does not contain ZIF-8, but contains 30% ionic liquid, which is calculated as 30% of the sum of the mass of PEO and lithium salt. The specific preparation steps are as follows:

[0105] According to the molar ratio of 18:1, 0.881 g of PEO and 0.319 g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) were weighed, and 0.36 g of ionic liquid was weighed according to 30% of the sum of the mass of PEO and the lithium salt. The lithium salt was added into a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and after stirring to fully dissolve, the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, PEO was slowly added in two batches, and stirred vigorously while adding. After the addition was completed, constant temperature stirring was performed at 45°C for 24 hours, and the rotation speed was set to 230rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50°C for 48 hours to completely remove the residual acetonitrile solvent. After drying, a composite solid electrolyte D with an ionic liquid addition of 30% was obtained, but the film-forming property of D was very poor, and it was difficult to completely peel off on the mold and could not be punched and formed.

[0106] Comparative Example 5

[0107] To demonstrate the beneficial effects of the composite solid electrolyte, a PEO-based polymer electrolyte CPE0 without ZIF-8 nanoparticles was synthesized and compared.

[0108] Take the PEO and lithium salt in Example 1, according to the molar ratio of 18:1, weigh 0.881g of PEO and 0.319g of lithium bistrifluoromethanesulfonyl imide (LiTFSI), 0.24g of ionic liquid was calculated according to 20% of the sum of the mass of PEO and LiTFSI, and the lithium salt was added to a beaker containing 20ml of analytical pure anhydrous acetonitrile, stirred and fully dissolved, and then the ionic liquid was added. After the ionic liquid was evenly dispersed in the solution, PEO was slowly added in two batches, stirring while adding. After the addition was completed, constant temperature stirring was performed at 45°C for 24 hours, and the speed was set to 230rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth and flat polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally volatilize most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50°C for 48 hours to completely remove the residual acetonitrile solvent. The dried composite solid electrolyte was punched into circular sheets with a diameter of 19mm and stored in a glove box to obtain a solid electrolyte CPE0 with a ZIF-8 addition of 0%. The conductivity of CPE0 at room temperature is only 0.64×10 -6 S / cm, and the lithium ion transference number is 0.34.

[0109] Comparative Example 6

[0110] In order to demonstrate the beneficial effects of PEO-based composite solid electrolytes, a PEO-based polymer electrolyte CPE without ionic liquid was synthesized. * 20 and make a comparison.

[0111] Take the PEO and ZIF-8 nanoparticles in Example 1, according to the molar ratio of 18:1, weigh 0.881g of PEO and 0.319g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), take the ZIF-8 prepared in Example 1, and weigh 0.24g of ZIF-8 nanoparticle powder calculated according to 20% of the sum of the mass of PEO and lithium salt. The lithium salt was added to a beaker containing 20 ml of analytical pure anhydrous acetonitrile, and ZIF-8 nanoparticles were added after stirring for 4 hours until the nanoparticles were evenly distributed in the solution. PEO was slowly added in two batches while stirring. After the addition was completed, constant temperature stirring was performed at 45°C for 24 hours, and the speed was set to 230 rpm. After PEO was completely dissolved, the PEO mixture was cast into a smooth polytetrafluoroethylene mold by a casting method. After drying in a glove box for 24 hours to naturally evaporate most of the acetonitrile, the composite solid electrolyte was transferred to a vacuum drying oven and vacuum dried at 50°C for 48 hours to completely remove the residual acetonitrile solvent. The dried composite solid electrolyte was punched into circular sheets with a diameter of 19 mm and stored in a glove box to obtain a solid electrolyte CPE with a ZIF-8 addition of 20%.* 20.

[0112] Test Case

[0113] 1. Material characterization:

[0114] The materials prepared in Examples 1 to 5 and the material prepared in Comparative Example 1 were characterized by XRD and SEM. The results are as follows: Figures 1 to 3 As shown, Figure 1 The SEM test results of (a) and (b) show that the prepared ZIF-8 nanoparticles are uniform in size and have no obvious agglomeration phenomenon. They have obvious regular polyhedral morphology and their diameters are about tens of nanometers. Figure 1 The XRD diffraction peaks of (c) were compared with the standard simulation card (reference for the standard simulation card: Pan Y, Liu Y, Zeng G, et al. Rapid synthesis of zeolitic imidazolate framework-8 (ZIF-8) nanocrystals in an aqueous system [J]. Chemical Communications, 2011, 47 (7): 2071-2073). Obvious diffraction peaks appeared at 2θ of 7.4°, 12.7°, 16.4°, 19.6° and 24.5°. The characteristic peak spectrum of the sample ZIF-8 nanoparticles synthesized at room temperature is basically consistent with the standard ZIF-8 characteristic peak spectrum, indicating that the synthesized sample ZIF-8 nanoparticles are pure phase. Figure 2 The SEM image shows that PEO has good film-forming properties and its surface is flat and smooth. The wrinkles and cracks are caused by mold scratches and stress during film peeling. With the increase of the amount of ZIF-8 nanoparticles added, the surface of the composite solid electrolyte membrane gradually becomes rough and the flexibility of the membrane decreases, which may be caused by the intensification of local particle agglomeration. Figure 3 (a) and Figure 3 (b) The XRD test results of the composite solid electrolyte show that with the increase in the amount of ZIF-8 nanoparticles added, the heights of the two characteristic peaks of PEO at 19.3° and 23.4° decrease, proving that the incorporation of ZIF-8 effectively reduces the crystallinity of PEO.

[0115] 2. PEO-based composite solid electrolyte battery assembly and use for the following electrochemical performance tests:

[0116] (1) PEO-based composite solid electrolyte ion conductivity test:

[0117] In a glove box with an argon atmosphere (O2 < 0.1ppm, H2O < 0.1ppm), a metal stainless steel sheet with a thickness of 1.5mm and a diameter of 15.8mm and a PEO-based composite solid electrolyte were assembled in the order of positive electrode shell-steel sheet-PEO-based composite solid electrolyte-steel sheet-reed sheet-negative electrode shell. Examples 1 to 5 and comparative examples 1 to 5 (Comparative example 4 has poor film-forming properties and cannot be used) and the prepared composite solid electrolyte were assembled into a symmetrical battery and pressed with a tablet press. The assembled solid-state battery was placed in a 60°C oven and allowed to stand for 4 hours. After being taken out, the PEO-based composite solid electrolyte was tested with an electrochemical workstation at 20°C to 70°C for the AC impedance spectrum and the ionic conductivity was calculated, wherein the frequency range was 1000000Hz to 0.1Hz and the amplitude was 10mV.

[0118] like Figure 4 As shown, at room temperature, with the increase of the amount of ionic liquid added, the ionic conductivity of the solid electrolyte increases significantly, the texture of the solid electrolyte becomes softer and softer, and the film-forming performance decreases significantly. If the amount added exceeds 30%, the solid electrolyte will be unusable. Taking all factors into consideration, the amount of ionic liquid added to the composite solid electrolyte should be 20%.

[0119] like Figure 5 As shown, Figure 5 (a) is the AC impedance diagram of the PEO-based composite solid electrolyte at room temperature (25°C). It can be seen that the conductivity of the PEO-based composite solid electrolyte at room temperature increases with the increase in the amount of nanoparticles added. The addition of 20wt% ZIF-8 nanoparticles has the highest conductivity of 4.9×10 -5 S / cm, which is much higher than that of pure PEO polymer electrolyte (at room temperature, the conductivity of pure PEO polymer electrolyte membrane is only 10 -7 When the added ZIF-8 nanoparticles exceed 20wt%, the conductivity of the PEO-based composite solid electrolyte decreases. This is because the excessive amount of nanoparticles added further intensifies the agglomeration phenomenon, blocks the lithium ion migration channel, deteriorates the interface contact, and reduces the overall conductivity of the PEO-based composite solid electrolyte. This is also related to Figure 2 The SEM image of (a) is consistent. At room temperature, the PEO-based composite solid electrolyte CPE20 shows the smallest impedance, corresponding to a conductivity of 4.9×10 -5 S / cm; Figure 5 The temperature-conductivity (T-σ) diagram (b) shows that the conductivity of the PEO-based composite solid electrolyte increases with increasing temperature, and the growth trend is most obvious around 60°C. This is because at 60°C, PEO is close to its melting point, the crystallinity decreases significantly, and the movement of PEO chains is more active. At 60°C, the ionic conductivity of CPE20 reaches 1.0×10 -3S / cm, take the logarithm of conductivity (σ) and make a scatter plot with the temperature of 1000 / T, such as Figure 5 (c) It can be seen that it is a linear relationship, which conforms to the law of the Arrhenius equation.

[0120] (2) PEO-based composite solid electrolyte ion migration number test:

[0121] Take the CPE20 obtained in Examples 1 to 5 and the CPE0 obtained in Comparative Example 5, assemble a 2032 battery in the glove box in the order of positive electrode shell-lithium sheet-PEO-based composite solid electrolyte-lithium sheet-steel sheet-reed sheet-negative electrode shell, and test the battery AC impedance with an electrochemical workstation after standing for 4 hours at 60°C to obtain R0, with a frequency range of 1000000 Hz-0.1 Hz, and then test the CA curve of the battery, with a test current of 10 mV and a time of 10800 s. Record the initial current I0 and the stable current I S Finally, test the AC impedance value R after the battery stabilizes. S . Figure 6 a and Figure 6 b is the current-time and impedance diagram before and after polarization of CPE20 constant current polarization. Figure 6 c and Figure 6 d is the current-time diagram of CPE0 constant current polarization and the impedance diagram before and after polarization. Figure 6 e is the lithium ion migration number of solid electrolytes with different proportions. According to the calculation formula of ion migration number, it is calculated that the ion migration number of CPE20 at 25°C is 0.48, the ion migration number of CPE0 is 0.34, the ion migration number of CPE5 is 0.40, the ion migration number of CPE10 is 0.44, the ion migration number of CPE15 is 0.46, and the ion migration number of CPE25 is 0.46. The lithium ion migration number of the solid electrolyte first increases and then decreases with the increase of MOFs addition. Excessive MOFs nanoparticles agglomerate. The unique porous structure and large specific surface area of ​​ZIF-8 contain abundant Lewis acid centers, which are compatible with large anions containing F. — The interaction between lithium salts further promotes the dissociation of lithium salts. The addition of ionic liquids effectively increases the number of ion migration, thereby promoting the dissociation of lithium salts and improving Li + Content ratio.

[0122] (3) Electrochemical stability window test of PEO-based composite solid electrolyte:

[0123] Take CPE20 obtained in Example 1, CPE0 obtained in Comparative Example 5, and CPE obtained in Comparative Example 6. * 20. In a glove box, 2032 batteries were assembled in the order of positive electrode shell-lithium sheet-PEO-based composite solid electrolyte-steel sheet-reed sheet-negative electrode shell. After standing at 60°C for 4 hours, a linear sweep voltammetry test (LSV) was performed. Figure 7 Linear voltammetric scanning tests show that the electrochemical stability window of pure PEO polymer electrolyte is only about 4V, which is difficult to meet the requirements of practical use. * 20 can reach about 5V, while the electrochemical stability window of CPE20 is as high as 5.3V. The addition of MOFs can improve the electrochemical stability window of the composite solid electrolyte to a certain extent. Ionic liquids have an excellent electrochemical stability window, which significantly improves the interface contact, reduces the occurrence of side reactions during charging and discharging, and reduces current fluctuations. The excellent electrochemical stability window performance allows the composite solid electrolyte to match the high-voltage ternary cathode material.

[0124] (4) PEO-based composite solid electrolyte interface stability test:

[0125] Take the CPE20 obtained in Example 1 and the CPE0 obtained in Comparative Example 5, assemble 2032 batteries in the glove box in the order of positive electrode shell-lithium sheet-PEO-based composite solid electrolyte-lithium sheet-steel sheet-reed sheet-negative electrode shell, and perform cross-current charge and discharge tests on the charge and discharge cabinet after standing for 4 hours at 60°C. The charge and discharge current density is set to 100mA / cm 2 , each charge and discharge time is 30 minutes. Figure 8 The results show that at 100mA / cm 2 Under high current density, the polarization voltage of CPE0 without adding ZIF-8 nanoparticles is 0.18V, while that of CPE20 is only half of it. The smaller polarization voltage indicates that the compatibility between the electrolyte and the negative electrode is better after the addition of ZIF-8 nanoparticles. After 120 hours, the voltage platform of the pure PEO-based electrolyte suddenly dropped, indicating that it had a short circuit, while the polarization voltage of CPE20 did not show obvious fluctuations, showing good interface stability.

[0126] 3. Use solid electrolytes for electrochemical performance testing of half-cells:

[0127] Take the CPE20 obtained in Example 1 and the CPE0 obtained in Comparative Example 5, and assemble a 2032 all-solid electrolyte full battery in the glove box in the order of positive electrode shell-positive electrode material-PEO-based composite solid electrolyte-diaphragm-negative electrode material-gasket-shrapnel-negative electrode shell. Among them, preparation of positive electrode material: put super P and positive electrode active material (commercial lithium iron phosphate) into a mortar and grind them evenly, transfer them to a 10mL glass bottle, add 5% PVDF NMP solution, so that the mass of positive electrode active material, super P and PVDF in the mixed system is 8:1:1. After the mixed system is stirred evenly, it is spread on aluminum foil, and the mixed system is scraped into a film with a 150μm scraper. Finally, the positive electrode material is vacuum dried at 80°C for 24h to remove the organic solvent, and cut into original sheets with a diameter of 10mm after vacuum drying. The negative electrode of the half-cell is a metal lithium sheet. After assembly, it is left to stand at 60°C for 4 hours, and then the battery's charge and discharge curve is tested at a specific rate using Blue Power's CT-2001A battery testing system.

[0128] Fig. 9 (a) and Fig. 9 (b) shows that at a current density of 0.1C, the first discharge capacity of the battery LiFePO4||CPE20||Li reaches 135.4mAh / g, while for the battery LiFePO4||CPE0||Li under the same conditions, the first discharge capacity is only 119.3mAh / g. The capacity retention rate of the battery LiFePO4||CPE20||Li after 20 cycles is 98.2%, while the capacity retention rate of the battery assembled with unmodified materials is only 96.6%. Fig. 9 (c) and Fig. 9 (d) shows that at a high current density of 0.5C, the battery LiFePO4||CPE20||Li has an initial discharge capacity of 120.5mAh / g, while the battery LiFePO4||CPE0||Li without the addition of ZIF-8 nanoparticles has an initial discharge capacity of only 94.1mAh / g. After 50 cycles at a high current density, the capacity retention rate of LiFePO4||CPE20||Li is 96.1%, which is higher than the 94.5% test result of LiFePO4 / CPE0 / Li material. At the same time, the platform voltage difference of LiFePO4||CPE20||Li during charge and discharge is significantly smaller than that of LiFePO4||CPE0||Li, which also shows that CPE20 has better interface contact performance.

[0129] The above experiments prove that the PEO-based composite solid electrolyte of the present invention can operate the battery normally, improve the conductivity of the pure polymer solid electrolyte, broaden its electrochemical stability window, and improve the contact between the electrolyte and the negative electrode, and has great application prospects in the field of new energy solid-state energy storage batteries.

[0130] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A PEO-based composite solid electrolyte, characterized in that: It is composed of PEO, MOFs, lithium salt and ionic liquid; The MOFs are ZIF-8 nanoparticles; The lithium salt is lithium bis(trifluoromethanesulfonyl imide); The ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt; The amount of the ZIF-8 nanoparticles is 0-25% of the sum of the mass of PEO and the lithium salt, excluding the endpoint value of 0; The dosage of the ionic liquid is 19-21% of the total mass of PEO, lithium salt and MOFs.

2. The method for preparing the PEO-based composite solid electrolyte according to claim 1, characterized in that: The solution mixing method is used to evenly distribute nano-scale MOFs particles and lithium salts in PEO, and ionic liquid is added as a plasticizer. A multi-ion channel network is formed, and finally the PEO mixed solution is poured into a mold and dried to obtain a composite solid electrolyte.

3. The method for preparing a PEO-based composite solid electrolyte according to claim 2, characterized in that The steps include: (1) Preparation of ZIF-8 nanoparticles: dissolving zinc salt with solvent A to obtain solution A; dissolving 2-methylimidazole with solvent B to obtain solution B; ultrasonically treating solution A and solution B, mixing them, stirring at a constant temperature, and standing them to separate the solid and the liquid; washing and drying the obtained solid to obtain ZIF-8 nanoparticles; (2) Preparation of ionic liquid: lithium salt and 1-ethyl-3-methylimidazolium bromide are mixed in a molar ratio of 1:1.1-1.3, solvent C is added to dissolve, stirred at a constant temperature, and allowed to stand. After the solution is separated into layers, the lower layer of oily liquid is taken out for washing, and then dried to remove the residual solvent to obtain a pure ionic liquid; (3) Preparation of composite solid electrolyte: Add lithium salt and ionic liquid to solvent D. After they are completely dissolved, add ZIF-8 nanoparticles. After the ZIF-8 nanoparticles are evenly dispersed, add PEO. Stir at a constant temperature and then pour the mixed solution into a mold and dry to obtain a PEO-based composite solid electrolyte.

4. The method for preparing a PEO-based composite solid electrolyte according to claim 3, characterized in that The steps include: The zinc salt described in step (1) is zinc nitrate hexahydrate; The solvent A in step (1) is at least one of water and methanol; The solvent B in step (1) is at least one of water and methanol; The solution used in the washing in step (1) is methanol; The lithium salt described in step (2) is lithium bis(trifluoromethanesulfonyl)imide; The solvent C described in step (2) is deionized water; The solution used in the washing in step (2) is deionized water; The solvent D in step (3) is anhydrous acetonitrile; The lithium salt described in step (3) is lithium bis(trifluoromethanesulfonyl)imide; The PEO described in step (3) has a molecular weight of 500,000 to 700,000.

5. The method for preparing a PEO-based composite solid electrolyte according to claim 3, characterized in that: The zinc salt described in step (1) and the 2-methylimidazole described are mixed in a mass ratio of 1:3.5-4.5; The molar ratio of PEO to lithium salt in step (3) is 17-19:1; The amount of ZIF-8 nanoparticles used in step (3) is 0-25% of the sum of the mass of PEO and lithium salt, excluding the endpoint value of 0; The amount of the ionic liquid used in step (3) is 19-21% of the total mass of PEO, lithium salt and MOFs.

6. The method for preparing a PEO-based composite solid electrolyte according to claim 3, characterized in that: The ultrasonic treatment conditions in step (1) are: 200-400W for 10-30 minutes; The stirring conditions in step (1) are as follows: temperature of 45-55° C., rotation speed of 250-400 rpm, and stirring time of 3-5 hours; The standing time in step (1) is 20 to 28 hours; The solid-liquid separation method in step (1) is centrifugation; The drying in step (1) is performed by drying at 50-70°C for 36-60 hours, grinding, and then drying at 90-100°C for 10-15 hours; The conditions for the constant temperature stirring in step (2) are as follows: temperature of 60-80°C, stirring time of 20-28 hours, and rotation speed of 250-350 rpm; The standing time in step (2) is 20 to 28 hours; The drying condition in step (2) is drying in a vacuum drying oven at 100-140° C. for 8-16 hours; The conditions for the constant temperature stirring in step (3) are as follows: temperature of 40-50°C, time of 20-30h, and rotation speed of 200-300rpm; The drying in step (3) is first drying in a glove box and then drying in a vacuum drying oven.

7. The method for preparing a PEO-based composite solid electrolyte according to claim 6, characterized in that: The centrifugal condition is 8000-10000 rpm for 3-10 min; The drying in the glove box is to place the mold containing the mixed solution in the glove box for 12 to 48 hours; The glove box is in an argon atmosphere with water and oxygen concentrations controlled below 0.1 ppm; The drying temperature in the vacuum drying oven is 40-60°C; The drying time in the vacuum drying oven is 36 to 72 hours.

8. A PEO-based composite solid electrolyte, characterized in that: The method is obtained by the preparation method according to any one of claims 2 to 7.

9. Use of the PEO-based composite solid electrolyte according to claim 1 in manufacturing batteries.

Citation Information

Patent Citations

  • Preparation method of gel-type ionic liquid / polymer electrolyte

    CN103682434A

  • Solid-state lithium ion composite electrolyte membrane and preparation method thereof

    CN111048829A